Experimental and numerical investigation of methane thermal partial oxidation in a small-scale porous media reformer. (5th January 2017) - Loukou, A.; Mendes, M.A.A.; Frenzel, I.; Pereira, J.M.C.; Ray, S.; Pereira, J.C.F.; Trimis, D.
Abstract: This study deals with the topic of synthesis gas (syngas) production from preheated, rich methane/air mixtures. The examined process is based on non-catalytic partial oxidation within a small-scale porous media based reformer, intended for application in Solid Oxide Fuel Cell (SOFC) based systems. For this purpose, process characteristics like temperature profiles within the porous material and exhaust syngas compositions were experimentally and numerically investigated under conditions that can be encountered in such systems. The soot content of the generated syngas was also measured using the technique of Scanning Mobility Particle Sizing. An important feature of the reformer, which was demonstrated during the experiments for a wide range of thermal loads (380–1895 kW/m 2 ) and equivalence ratios (1.9–2.6), is the ability to operate based on stationary flames. This is achieved using a two-section design. The sections show a conical and a cylindrical geometry, whereas the same porous medium is installed in both of them. For this study, the solid matrix was created as packed bed of Al2 O3 -Raschig rings (62% open porosity). The process was simulated with a quasi-1D numerical model, which uses a volume-averaged approach. The model solves both the gas- and solid-phase energy balances explicitly and accounts for the radiative heat transport in the solid-phase. Peak temperatures measured within the porous zone provide evidence of superadiabatic combustion, which is also confirmed by the numerically predicted temperature profiles with the model. Syngas compositions reveal a maximum reforming efficiency of 65% based on H2 and CO, while the soot limit of the process was found to lie at φ  = 2.2, regardless of thermal load and preheat temperature of the fresh mixture. Highlights: Syngas production from methane thermal partial oxidation in porous media reformer. Stationary flame stabilization method for premixed combustion of preheated mixtures. Experimental characterization of reformer for range of typical conditions. System 1D modelling and simulation validated against experiments. Results show evidence of superadiabatic combustion and good process performance.